Genetic differentiation of yellowfin sole ( Limanda aspera) from the Tauiskaya Guba Bay revealed on nucleotide sequences in fragment of the gene of cytochrome b mtDNA - Sergey P. Pustovoit; Ravil R. Yusupov (Известия ТИНРО)
Genetic diversity of yellowfin sole from the northern Okhotsk Sea is considered for the first time. The genetic differentiation is investigated for six samples of this flounder species spawning in the Tauiskaya Guba Bay (159 specimens in total), and 57 haplotypes are revealed on nucleotide sequences in fragment of the gene of cytochrome b . Average haplotype diversity for all specimens is 0.870. Two groups of the flounders typical for the eastern and western parts of the bay could be divided by the value of genetic differentiation with the coefficient of nucleotide differentiation between them NST = 0.0309. This structure of the yellowfin sole spawning stock should be accounted in management of the flounders fishery in the Tauiskaya Guba Bay.